ANALISIS KESULITAN MEMBACA TEKS BAHASA INGGRIS PADA SISWA KELAS III DI SD ISLAM AT-THAHIRIN KOTA TANGERANG - Sunaryo; Rizki Zuliani; Balqis Syifa Fauziyyah (STKIP Subang, 2023)
This study aims to find out the problems texts in English learning at grade 3 at At-Thahirin Islamic Elementary School. This study used a qualitative descriptive techniques in the form of reading ability tests, teacher interviews, observation and documentation. Check the validity of the data using triangulation. Data is analyzed through the steps of data collection, data reduction, data presentation and drawing conclusions. Respondents in this study amounted to 7 people, namely 1 teacher and 6 students from grade 3.